Pancreatic Mucinous Cystic Neoplasm with Associated Invasive Carcinoma: A Case Report and Literature Review - Marcinkeviciute, Kristina; Jurkeviciute, Digne; Stulpinas, Rokas; Stratilatovas, Eugenijus; Dulskas, Audrius (Lietuvos chirurgija, 2023)
Background. Pancreatic mucinous cystic neoplasm (PMCN) with associated invasive carcinoma is a rare entity. According to the World Health Organisation (WHO) 2010, PMCN with associated invasive carcinoma is referred to the malignant lesions of the pancreatic epithelial tumour. Case report. A 52-year-old female patient presented with pain in the umbilical and epigastric regions for 5 months and noticed a solid visible tumour on the left side of the abdomen 3 months ago when she lied down. The level of the CA125 was 47.64 U/ml (normal value <35 U/ml). Abdominal and pelvic magnetic resonance imaging (MRI) showed a cystic multiseptal mass in the left iliac region, defined as a left ovary tumour, while Computed tomography scan revealed a cystic tumour of the pancreatic tail. The patient underwent a resection of the pancreatic tail with a 20 cm cystic solid tumour, splenectomy and left hemicolectomy. Histopathology report confirmed mucinous cystic neoplasm of the pancreatic tail with associated invasive carcinoma (combined badly differentiated (G3) ductal (40%) and undifferentiated (G4) anaplastic (60%) carcinoma) pT1bN0. Postoperative course complicated with wound infection. The patient was discharged on postoperative day 10. The patient is still alive 2 years on follow-up. Conclusions. PMCN with associated invasive carcinomas are rare lesions of pancreas with relatively benign course. This malignant pancreatic tumour displays morphologies as pleomorphic epithelial cells and relatively mononuclear spindle cells, and not always tends to have underlying ovarian type stroma. The comprehensive histopathological examination of the tumour is necessary in order to cure most MCN patients with minimally invasive types.